Diversity and assembly of root-associated microbiomes of rubber trees - Lan, Guoyu; Wei, Yaqing; Li, Yuwu; Wu, Zhixiang (Frontiers in Plant Science, 2023)
Understanding the diversity and assembly of the microbiomes of plant roots is crucial to manipulate them for sustainable ecosystem functioning. However, there are few reports about microbial communities at a continuous ﬁne-scale of roots for large trees. We investigate the structure, diversity and assembly of bacterial and fungal community for soil (non-rhizosphere), rhizosphere, and rhizoplane as well as root endosphere of rubber trees. The microbial source track results revealed 18.69% bacterial and 20.20% fungal OTUs in rhizoplane derived from endosphere, and 20.64 % bacterial and 20.60 % fungal OTUs from soil. This suggested that rhizoplane microbial community was a mixed community of soil and endoshperhe microbial communities, and microorganisms can disperse bidirectional across different compartments of plant root. No enriched or depleted core bacterial and fungal OTUs in rhizosphere, little differences in microbial compositions as well as more shared edges of network structure between soil and rhizosphere highlights the theory that rhizosphere microbial community is a subset of soil community. A large number of functional genes (such as nitrogen fixation, nitrite reduction) and more enriched core OTUs in the root rhizoplane, which results in a less stability but more complex of network structure. This demonstrated that rhizoplane is the most active compartment and a hotspot of plant-soil-environment interactions. Rhizoplane bacterial and fungal community, which were shaped by both environment variables and plant genetic factors, were more stochastic than those of rhizosphere and soil. Our study expand our understanding of root associated microbial community structure and function, which may provide the scientific basis for sustainable agriculture through biological process management.